The complete genome sequence of EC1-UPM, a novel N4-like bacteriophage that infects Escherichia coli O78:K80 - Gan, Han Ming; Sieo, Chin Chin; Gee, Shirley Hoon Tang; Omar, Abdul Rahman; Ho, Yin Wan (BioMed Central, 2013)
Bacteriophage EC1-UPM is an N4-like bacteriophage which specifically infects Escherichia coli O78:K80, an avian pathogenic strain that causes colibacillosis in poultry. The complete genome sequence of bacteriophage EC1-UPM was analysed and compared with other closely related N4-like phage groups to assess their genetic similarities and differences.Bacteriophage EC1-UPM displays a very similar codon usage profile with its host and does not contain any tRNA gene. Comparative genomics analysis reveals close resemblance of bacteriophage EC1-UPM to three N4-like bacteriophages namely vB_EcoP_G7C, IME11 and KBNP21 with a total of 44 protein coding genes shared at 70% identity threshold. The genomic region coding for the tail fiber protein was found to be unique in bacteriophage EC1-UPM. Further annotation of the tail fiber protein using HHpred, a highly sensitive homology detection tool, reveals the presence of protein structure homologous to various polysaccharide processing proteins in its Cterminus. Leveraging on the availability of multiple N4-like bacteriophage genome sequences, the core genes of N4-like bacteriophages were identified and used to perform a multilocus phylogenetic analysis which enabled the construction of a phylogenetic tree with higher confidence than phylogenetic trees based on single genes. We report for the first time the complete genome sequence of a N4-like bacteriophage which is lytic against avian pathogenic Escherichia coli O78:K80. A novel 928 amino acid residues tail fiber protein was identified in EC1-UPM which may be useful to further the understanding of phage-host specificity. Multilocus phylogenetic analysis using core genes of sequenced N4-like phages showed that the evolutionary relationship correlated well with the pattern of host specificity.